RESPON PERTUMBUHAN DAN PRODUKSI KACANG PANJANG (Vigna sinensis L.) TERHADAP PEMBERIAN PUPUK KANDANG KAMBING - Kutanggas, Yohana Romolda; Maruapey, Ajang; Sangadji, Zulkarnain Sangadji (Universitas Tribhuwana Tunggadewi, 2024)
This research aimed to determine the response of growth and yield of long bean plants to the application of organic goat manure fertilizer. The experiment used a randomized block design consisting of 4 treatments such as K0 = No fertilizer (control), K1 = 2 kg/goat manure plot, K2 = 3 kg/goat manure plot, and K3=6 kg/goat manure plot. The treatment was repeated three times. Each experimental plot contained 25 plants. Five plants from each plot were selected as samples. The results showed that the treatment with a dose of 7 kg/plot produced the highest long bean yields of 13.53 kg/plot and 8.22 t/ha, respectively. A fertilizer dose of 7 kg/plot is the recommended dose for the farmer when planting long beans.